PROBLEMATIKA PELAKSANAAN PENDAFTARAN TANAH MELALUI PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KOTA BATU - Ayu, Isdiyana Kusuma (Faculty of Law, University of Muhammadiyah Malang, 2019)
Systematic and Complete Land Registration (PTSL) is a program organized by the Government to assist the public in obtaining the certificate of the land. Batu City is one of the cities in Indonesia that follow to help communities that PTSL majority among those yet to register their land to Office land Batu City. The purpose of this research is to describe the implementation of PTSL in Batu City and analyze its land registry through systematic land registration in Batu City and the efforts complete. The method used in this research is juridical-empiric research method using juridical sociological approach. The role of Councilor and community groups are very important in the implementation of PTSL in Batu City. Problems found in the implementation of PTSL in Batu City, namely the object ground warranted, a period of physical and juridical data announcement 14 working days, an affidavit of Ownership in good faith as a replacement deed of passage, delay in paying taxes of the land, the lack of human resources, and Absentee Land and The forbidden land in Batu City.